Sedimentation Dynamics and Sustainable Lake Management: Integrating Bathymetric Analysis and Tri Hita Karana in Lake Tamblingan - Luh Ayu Putri Wedayanti Pulasari; I Dewa Ayu Meia Damayanthi; Ni Luh Putri Prabandari (Universitas Pendidikan Nasional, 2026)
Lakes play an important role in supporting freshwater resources, ecosystems, and socio-cultural activities. However, increasing sedimentation has become a major environmental issue that can affect lake morphology and ecological functions. This study aims to analyze sediment accumulation in Lake Tamblingan and interpret its implications using the Tri Hita Karana framework. Bathymetric surveys were conducted using a Midas Valeport single-beam echosounder with 200 m transect spacing. The data were processed using Civil 3D and ArcGIS to generate bathymetric maps for 2023 and 2024, and sediment thickness was estimated through depth comparison. The results show that Lake Tamblingan experienced sediment accumulation reaching approximately 1,56 m, indicating a significant lake shallowing process. This condition may reduce lake storage capacity, increase turbidity, and potentially affect ecological stability as well as socio-cultural activities surrounding the lake. Integrating bathymetric analysis with the Tri Hita Karana perspective highlights the importance of holistic lake management that considers environmental, social, and spiritual dimensions.